2000
DOI: 10.1106/7fwa-3vlf-ttut-jaea
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Matrix Woven Fabric Composites Subjected to Low Velocity Impact: Part II-Effect of Plate Thickness

Abstract: The studies have been carried out on the damage initiation behavior of polymer matrix woven fabric (WF) composite plates subjected to a transverse central low velocity point impact load. Specifically, the effect of composite plate thickness on the impact behavior has been investigated with a square plate of 150 mm x 150 mm with thicknesses varying from 4.5 mm to 8.0 mm. The material systems considered are: E-glass/epoxy and T300/5208 carbon/epoxy. Inplane failure of the layers in the form of matrix cracking/la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 4 publications
0
12
0
2
Order By: Relevance
“…Carbon and glass fibre composites have been the most studied under impact loading. [1][2][3][4][5][6][7][8][9] Of these, Naik et al 3,4 investigated the impact behaviour of E-glass/ epoxy and T300/5208 carbon/epoxy composites using the finite element analysis method. The results indicated that both carbon and glass woven fabric-laminated composites showed a similar trend with the composites thickness, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon and glass fibre composites have been the most studied under impact loading. [1][2][3][4][5][6][7][8][9] Of these, Naik et al 3,4 investigated the impact behaviour of E-glass/ epoxy and T300/5208 carbon/epoxy composites using the finite element analysis method. The results indicated that both carbon and glass woven fabric-laminated composites showed a similar trend with the composites thickness, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies on the effect of plate thickness on the behavior of polymer matrix WF composites subjected to low velocity impact is presented in Reference [26].…”
Section: Effect Of Incident Impact Velocity and Impactor Massmentioning
confidence: 91%
“…In our earlier studies [12], using nite element analysis, a segmented linear relationship was observed between the peak contact force and the composite plate thickness during low velocity impact. Kim and Kang [13] carried out analytical and experimental transverse impact studies on plain weave glass/epoxy composite plates having various thicknesses.…”
Section: Introductionmentioning
confidence: 94%